The Influence of Students' Educational Background on Learning Outcomes in English Subjects at MA Pesantren Tarbiyah Takalar - Pratiwi, Hedriana; Farahdiba, Syarifah; G, Hasriani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research aims to determine the influence of students' educational background on learning outcomes in English subject. This type of research is ex post facto quantitative research. This research was conducted to determine the causes or reasons for the existence of differences in behavior or status of individual groups. The sample in this research was students of MA Pesantren Tarbiyah Takalar classes Xa and Xb, totaling 45 students. The research instruments used are questionnaires and documentation of learning outcomes. The questionnaires given to students contains 10 questions about educational background and documentation of learning outcomes used to determine students' learning outcomes by looking at the learning outcome report. Data were analyzed using descriptive statistics and inferential statistics. The research results show that ?count = 0,118 and ?????? = 2,016 so ?count < ?????? (0,118 < 2,016) means that there is no influence of students' educational background on learning outcomes in English subject at MA Pesantren Tarbiyah Takalar.